Penetapan Harga Pokok Produksi Menggunakan Metode Full Costing Dalam UMKM Franchise Hoola Drinks - Nabilah Syukurilah; Whury Fitria Rahma; Kholida Atiyatul Maula (Peneliti.net, 2023)
The production cost of Hoola MSME drinks is determined by adding up the costs of raw materials, direct labor, variable production costs and fixed production costs. The cumulative cost result is then divided by the number of times per month ie. H. in May, divided by the units sold to determine the unit price. Because the UMKM Hoola Drinks only records buying and selling transactions, the purpose of this research is to determine the cost of production of the drink. The survey was conducted through direct interviews with Hoola Beverage MSME entrepreneurs as basic information producers. The full cost method is also used to calculate the production cost of Rp. 7.115.